Study guides

☆☆

Q: If 1x = x and x = x than what does x equal?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.

Depends... 1* x = x but 1^x does NOT = x, if x not = 1 or -1

1x - 39 = 76 1x + -39 = 76 39 = 39 1x + -39 + 39 = 76 + 39 1x + 0 = 115 X = 115 Check 1x -- 39 = 76 If x = 115 1 * 115 -- 39 = 76 115 -- 39 = 76 115 + -39 = 76 76 = 76

x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3

1x

Related questions

One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.One to any power is equal to 1. As a formula: For all x, 1x = 1.

There is always a 1 in front of the x but the 1 is invisible so it same as 1x + 1x = 2x x + x = 2x

x = 0

Depends... 1* x = x but 1^x does NOT = x, if x not = 1 or -1

x/1 + x/x = 84 where x = a prime number that is divisible by 1 and itself. Then find common denominator of 1x. Then we have x squared/1x + x/1x = 84. To simplify this will be x squared + x/1x = 84. The this becomes 1 + x = 84. Then x = 83. The prime numbers are 1 and 83 which fit the equation.

2x-1x or x equals 1x or x 2x-x=x

if is (x-6)-(1x-1) = -5 if id (x-6)-(1x+1) = -7

1 + 1 + 1 + 1 + 1x = 4 + x

1x - 39 = 76 1x + -39 = 76 39 = 39 1x + -39 + 39 = 76 + 39 1x + 0 = 115 X = 115 Check 1x -- 39 = 76 If x = 115 1 * 115 -- 39 = 76 115 -- 39 = 76 115 + -39 = 76 76 = 76

1

It can be simplified to: x-5y

x + 3 + 2x = x + 9 x + 2x + 3 = x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 1x - 1x + 2x + 3 = 1x - 1x + 9 2x + 3 = 9 2x + 3 - 3 = 9 - 3 2x + 3 - 3 = 9 - 3 2x = 9 -3 2x = 6 2x/2 = 6/2 2x/2 = 6/2 x = 6/2 x = 3

People also asked